A clusterized energy management with linearized losses in the presence of multiple types of distributed generation. (December 2019) - Rigo-Mariani, Rémy; Ling, Keck Voon; Maciejowski, Jan
Highlights: A modified DC Power Flow with a piecewise linearization of the branch losses based on a modified power balance at the buses. The consideration of controllable loads as distribution assets based on load shifting for chemical plants. A partitioning method whose distance computation ensures the cluster connectedness. The implementation of a fast sequential management procedure with zonal and nodal representations. Abstract: This paper presents an optimal management (OM) strategy for distributed generation (DG) planning studies. The objective is the reduction of the CO2 emissions for the power generation on Jurong Island in Singapore. Different DG resources are investigated with solar panels, energy storage units, small gas turbines as well as controllable loads in addition to the centralized generation already in site. Each of those resources is modeled in an optimal scheduling procedure that furtherly allows to test several DG configurations (i.e. different types/sizes/sites) with regards to the CO2 emissions. The paper mainly focuses on the implementation of the OM and the main challenge is to avoid prohibitive computational times, which is tackled thanks to two approaches. At first, a linearization of the line losses with a modified DC power flow is considered while optimizing the system management over a representative day. A generic clustering method is then developed along with a sequential optimal management (S-OM) lying on both nodal and zonal representations of the electrical network. Different validation tests are performed as well as sets of simulations with several DG configurations. The optimal DG planning procedure itself is not in the scope of that paper and will be part of further developments.